ANALISIS EFEKTIVITAS DAN KONTRIBUSI PENERIMAAN BPHTB TERHADAP PENDAPATAN ASLI DAERAH KABUPATEN SIDOARJO - Nourma Yunita; Dian Fahriani (Universitas Nahdlatul Ulama Sidoarjo, 2020)
The purpose of this study is to determine the effectiveness level of land and building rights acquisition fees (BPHTB) and the contribution that land and building rights acquisition fees (BPHTB) provide to local revenue(PAD) in Sidoarjo Regency. The research method used is descriptive qualitative with primary and secondary data sources. Based on the results of research from 2015 to 2019, the following results were obtained: (1) In 2015, the acquisition fee for land and building rights (BPHTB) was 101.08% and increased in 2016 to 114.03%, then in 2017 it increased again by 128.85% in 2018 decreased by 113.02% and increased again in 2019 amounting to 109.15% the effectiveness of land and building land acquisition duties (BPHTB) in Sidoarjo Regency with a very effective value interpretation, with an average effectiveness rate of receiving land and building (BPHTB) fees for five years at 113%. (2) Contribution of land and building rights acquisition fees (BPHTB) to local revenue (PAD) in Sidoarjo Regency in 2015 with a percentage of 17.38%, decreased in 2016 by 17.02%, and increased again in 2017 amounted to 20.19% in 2018 decreased again by 19.76% and experienced an increase again in 2019 by 19.76% of the contribution of land and building acquisition duties (BPHTB )in Sidoarjo Regency for 5 years showing value interpretation less with a percentage of 18.51%. (3) The source of local revenue in Sidoarjo Regency does not only come from the tax on the acquisition of land and building rights (BPHTB), but there are other local taxes, regional levies, and others that are included in the component of regional revenue (PAD).